2019
DOI: 10.1038/s41419-019-1765-0
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA Rpph1 promotes inflammation and proliferation of mesangial cells in diabetic nephropathy via an interaction with Gal-3

Abstract: Diabetic nephropathy (DN) is one of the most significant complications of diabetes and is the primary cause of end-stage kidney disease. Cumulating evidence has shown that renal inflammation plays a role in the development and progression of DN, but the exact cellular mechanisms are unclear. Irregular expression of long non-coding RNAs (lncRNAs) is present in many diseases, including DN. However, the relationship between lncRNAs and inflammation in DN is unclear. In this study, we identified differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 59 publications
(57 reference statements)
3
57
0
1
Order By: Relevance
“…Rpph1 was shown to bind Gal-3, a biomarker of diabetic nephropathy, which itself was increased in diseased renal tissue and enhanced mesangial cells proliferation. Further experiments suggested that Rpph1 somehow enhances the expression of Gal-3, which itself was shown to play a role in the regulation of inflammation and proliferation of mesangial cells via the Mek/ Erk pathway (Zhang et al 2019).…”
Section: Rpph1mentioning
confidence: 99%
“…Rpph1 was shown to bind Gal-3, a biomarker of diabetic nephropathy, which itself was increased in diseased renal tissue and enhanced mesangial cells proliferation. Further experiments suggested that Rpph1 somehow enhances the expression of Gal-3, which itself was shown to play a role in the regulation of inflammation and proliferation of mesangial cells via the Mek/ Erk pathway (Zhang et al 2019).…”
Section: Rpph1mentioning
confidence: 99%
“…Studies have also begun to demonstrate the participation and regulatory mechanism of non-coding rnas (ncrnas) on dn development (6,7). circular rnas (circrnas) are a novel class of endogenous ncrnas, which mediate diverse physiological and pathological changes in the human body (8), including dn, and are characterized by a covalently-closed loop formed by back-splicing between the 5' to 3' ends of the polya tail (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…RPPH1 is also thought to be involved in the inflammatory pathogenesis of diabetic nephropathy. Indeed, in a mouse model of diabetic nephropathy, RPPH1 was abnormally overexpressed in renal tissue and enhanced the release of inflammatory cytokines, including tumor necrosis factor-α and monocyte chemotactic protein-1 (9). Moreover, Zhang et al (10) demonstrated that RPPH1 upregulation enhanced the proliferative and colony formation abilities of breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%